Fractal modes and multi-beam generation from hybrid microlaser resonators - José A. Rivera (Nature Portfolio, 2018)
Although fractal optical patterns have been realized previously, the direct generation of fractal modes from a laser has proven challenging. Here, Rivera et al. modify an optical cavity with a microsphere array to produce fractal laser modes and probe live cells, which serve as a component of the resonator.